2000
DOI: 10.1677/joe.0.1650537
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I and IGF-I-binding proteins in rats with adjuvant-induced arthritis given recombinant human growth hormone

Abstract: Adjuvant-induced arthritis in rats is associated with growth failure, hypermetabolism and accelerated protein breakdown. We have previously reported that adjuvant-induced arthritis in rats results in a decrease in body weight gain, pituitary GH mRNA, circulating GH and IGF-I together with an increase in serum IGF-binding proteins (IGFBPs). The aim of this study was to analyze the role of GH in the decrease in body weight and in the alterations in the IGF-I system observed in chronic inflammation.Male Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
(46 reference statements)
4
27
0
Order By: Relevance
“…The results showed that the high serum levels of IGFBP-3 in arthritic rats appear to be largely due to decreased proteolysis of IGFBP-3, since hepatic synthesis of IGFBP-3 was not changed. As we have already described in arthritic rats (Ibáñez de Cáceres et al 2000), concentrations of IGFBP-3 in serum are increased and GH treatment prevents this increase. These changes in serum protein concentrations did not correlate with the hepatic synthesis of IGFBP-3, since liver IGFBP-3 mRNA content was not modified by arthritis and the synthesis remained constant in response to GH.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The results showed that the high serum levels of IGFBP-3 in arthritic rats appear to be largely due to decreased proteolysis of IGFBP-3, since hepatic synthesis of IGFBP-3 was not changed. As we have already described in arthritic rats (Ibáñez de Cáceres et al 2000), concentrations of IGFBP-3 in serum are increased and GH treatment prevents this increase. These changes in serum protein concentrations did not correlate with the hepatic synthesis of IGFBP-3, since liver IGFBP-3 mRNA content was not modified by arthritis and the synthesis remained constant in response to GH.…”
Section: Discussionsupporting
confidence: 65%
“…We have previously observed an increase in serum IGFBP-3 in arthritic rats, and found that GH administration prevents this increase (Ibáñez de Cáceres et al 2000). Therefore, the aim of this work was to study the mechanism responsible for the increase in serum IGFBP-3 in arthritic rats, by evaluating hepatic synthesis and proteolysis of IGFBP-3 in the serum.…”
Section: Introductionmentioning
confidence: 98%
“…Arthritic rats have low serum IGF1 levels that are inversely related to body weight gain (López-Calderón et al 1999), whereas chronic GH administration to arthritic rats increases body weight and serum IGF1 levels (Ibañez de Cáceres et al 2000). Similarly, GH administration to juvenile RA patients increases growth (Touati et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant-induced arthritis is an animal model for chronic inflammation and rheumatoid arthritis characterized by a decrease in body weight and cachexia (Roubenoff et al 1997, Ibáñez de Cáceres et al 2000. Cachexia, which also prevails in other situations such as burns, sepsis and cancer, is characterized by anorexia and tissue wasting, reflected essentially in a loss of adipose tissue and skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%